Effect of New Zealand Blackcurrant Extract on Cycling Performance and Substrate Oxidation in Normobaric Hypoxia in Trained Cyclists - Willems, Mark Elisabeth Theodorus (Sports (Basel), 2019)
New Zealand blackcurrant (NZBC) extract enhanced exercise-induced fat oxidation and 16.1 km cycling time trial (TT) in normobaric normoxia. The effect of NZBC extract on physiological and metabolic responses was examined during steady state cycling and a 16.1 km TT in normobaric hypoxia. This study used a randomized, double-blind, crossover design. Eleven healthy male cyclists (age: 38 ± 11 y, height: 179 ± 4 cm, body mass: 76 ± 8 kg, [Formula: see text] O(2max): 47 ± 5 mL·kg(−1)·min(−1), mean ± SD) ingested NZBC extract (600 mg·day(−1) CurraNZ® containing 210 mg anthocyanins) or a placebo (600 mg microcrystalline cellulose M102) for seven days (washout 14 days) and performed a steady state cycling test (3 × 10 min at 45%, 55% and 65% [Formula: see text] O(2max)) followed by a 16.1 km TT at a simulated altitude of ~2500 meters (~15% of O(2)). Indirect calorimetry was used to measure substrate oxidation during steady state cycling. Intake of NZBC extract had no effect on blood glucose and lactate, heart rate, substrate oxidation, and respiratory exchange ratio during steady state cycling at 45%, 55% and 65% [Formula: see text] O(2max), and on 16.1 km TT performance (placebo: 1685 ± 92 s, NZBC extract: 1685 ± 99 s, P = 0.97). Seven days intake of New Zealand blackcurrant extract does not change exercise-induced metabolic responses and 16.1 km cycling time trial performance for moderately endurance-trained men in normobaric hypoxia.